THE EFFECT OF INTERNAL CONTROL AND INTERNAL AUDIT ON FRAUD PREVENTION IN PROCUREMENT OF GOODS/SERVICES IN THE GOVERNMENT OF ROKAN HULU DISTRICT - Wutsqa, Urwatul; Daryatno, Andreas Bambang (Graduate Program of Universitas Tarumanagara, 2025)
Fraud in procurement of goods and services in government institutions is a wrong action and harms state finances and disrupts good procurement principles. This fraud can occur in various phases, starting from the planning, implementation, to supervision stages, and the results actually cause state losses and have a negative impact on society. The purpose of this study is to analyze the impact of internal control and internal audit with inspection to prevent fraud in government procurement of goods and services. This study uses primary data with all respondents of the regional workforce (SKPD). This involves the procurement of goods and services in the government regulated by the Rokan Hulu region. The sample selection technique in this study uses the technique targeted purposive sampling, and SPSS statistical tool for data analysis. The results of this study indicate that internal control and internal audit in fraud prevention affect the procurement of goods and services. The impact of this study is expected to be the basis for improving the internal control system and reducing the risk of irregularities in the procurement of goods and services by conducting internal audits.